Historical-critical pedagogy incorporation in science education: A dialectic critical analysis of a systematic bibliographic review - Massi, Luciana [UNESP]; De Souza, Bruno Novais [UNESP]; Sgarbosa, Evelin Carolina; Colturato, Andriel Rodrigo [UNESP] (Investigacoes em Ensino de Ciencias (IENCI), 2019)
This paper aimed to analyze on a critical and dialectical approach the incorporation of the Historical-Critical Pedagogy (HCP) by the researches in Science Education (SE). Through a review performed with diversified procedures based on the Historical-Dialectical Materialism, we identified works that related the HCP and the SE, including researches of the Environmental Education area. We identified 80 publications: Five papers of scientific journals, 28 works presented in scientific conferences, 29 dissertations, ten thesis, four chapters of books, and four whole books. In a first approach for data treatment, we performed a descriptive characterization of the works we found, observing the quantitative distribution of the different kinds of research through the years, the authors afiliation and their research groups. Then, we recovered categories from Marxism and HCP for analyze the works according to the dialectic logic. We discussed four categories that allowed us to deepen the understanding of HCP and its incorporation by the researches in SE: HCP as a historical, dialectical and materialist theory; the overcoming of pseudoconcreticity in HCP; the dialectical educational practice and the didactic moments of HCP; the dialectic mediation of HCP. Despite the meritorious efforts made by the authors to bring this pedagogy to the EC in an original and innovative way, the analysis developed through these categories indicate some recurrent aspects: A theorical-methodological eclecticism that relates the HCP to theories not grounded in Historical-Dialectical Materialism; a utilitarian concern that reduces the HCP to its form, identified with five determined steps, emptying it out of its content; an understanding of the social practice as synonymous of the immediate and everyday practice, removing the overcoming of pseudoconcreticity perspective; the absence of meaning of dialectic mediation in the five steps and in the role of school knowledge; an emptying out of catharsis sense, interpreted as an evaluation step or the conclusion of a didactic sequence. In short, we perceived an incorporation of the HCP of utilitarian nature and discussed the probable motives and implications for the construction of this pedagogy in SE.
Incorporacaõ da pedagogia histórico-crítica na educacaõ em ciências: Uma análise crítica dialética de uma revisaõ bibliográfica sistemática
Keywords: Critical review; Historical-critical pedagogy; Historical-dialectical materialism